Mutations in and deletions of the Ca2+ channel-encoding gene cacophony, which affect courtship song in Drosophila, have novel effects on heartbeating. - Ray, V.M.; Dowse, H.B. (Journal of Neurogenetics, 2005)
The cacophony (cac) locus of Drosophila melanogaster encodes the a-1 subunit of a voltage gated Ca(2+) channel, termed Dmca1A. A subset of mutations at this locus cause characteristic alterations in the male mating song, manifest as polycyclic pulses with higher than normal amplitude. This phenotype has been postulated to result from disruption of an oscillator involving the cac-encoded channel, nearly identical to a model proposed for the pacemaker of the Drosophila heart. We report here that flies bearing two intragenic mutations that affect song, cac(S) and cac(TS2), cause aberrant heartbeating. Hearts of both cac(S) and cac(TS2) mutants beat significantly more rapidly than wild type and the heartbeat is more regular across temperature. Deletions of the cac gene, heterozygous with cac(+), caused interestingly similar heartbeating anomalies. For the heart phenotypes, the mutations are dominant, unlike the effects of cac(S) on song. In sum, our results establish the hypothesis that the observed effects are a result of a reduced number of functional cac-encoded channels rather than any specific alteration in the protein, and that in addition to Dmca1A, a second Ca(2+) channel with different kinetics is also involved in pacemaking.